Experimental Therapy of Paracoccidioidomycosis Using P10-Primed Monocyte-Derived Dendritic Cells Isolated From Infected Mice - Silva, Leandro B. R.; Taira, Cleison L.; Dias, Lucas S.; Souza, Ana C. O.; Nosanchuk, Joshua D.; Travassos, Luiz R.; Taborda, Carlos P. (Frontiers in Microbiology, 2019)
Paracoccidioidomycosis (PCM) is an endemic mycosis in Latin American caused by the thermodimorphic fungi of the genus Paracoccidioides spp. Notably, a Th1 immune response is required to control PCM. In this context, dendritic cells (DCs) seem to be essential players in capture, processing and presentation of Paracoccidioides antigens to naïve T cells and their further activation. We have previously demonstrated that differentiated DCs from bone marrow cells, pulsed with the immunoprotective peptide 10 (P10), effectively control experimental PCM immunocompetent and immunosuppressed mice. However, this procedure may not be infeasible or it is limited for the therapy of human patients. Therefore, we have sought a less invasive but equally effective approach that would better mimics the autologous transplant of DC in a human patient. Here, we isolated and generated monocyte differentiated dendritic cells (MoDCs) from infected mice, pulsed them with P-10, and used them in the therapy of PCM in syngeneic mice. Similar to the results using BMDCs, the P10-pulsed MoDCs stimulated the proliferation of CD4+ T lymphocytes, induced a mixed production of Th1/Th2 cytokines and decreased the fungal burden in murine lungs in the setting of PCM. The process of differentiating MoDCs derived from an infected host, and subsequently used for therapy of PCM is much simpler than that for obtaining BMDCs, and represents a more reasonable approach to treat patients infected with Paracoccidioides. The results presented suggest that P10-primed MoDC may be a promising strategy to combat complicated PCM as well as to significantly shorten the lengthy requirements for treatment of patients with this fungal disease.